What do Palestinians and Jews-from-Arab-Lands Have in Common? : Nationalism and Ethnicity Examined Through the Compensation Question - Shenhav, Yehouda (Hagar: Studies in Society and Culture, 2000)
This article focuses on the immigration of Iraqi Jews to Israel in the early 1950s and examines the manner in which the Israeli State has used this immigration to offset the claims of the Palestinian national movement. It also sheds light on actions taken by WOJAC (World Organization of Jews from Arab Countries) to further Israel’s national interests, as well as on how these interests were challenged and re-formulated by WOJAC’s non-Israeli members. The history of WOJAC serves as an example of the anomalous relationship between nationality and ethnicity in the Zionist context. Lastly, this article underscores the conspicuous compartmentalization of ‘the Palestinian question’ and the ‘Mizrahi question’ within Israeli political and intellectual discourse.